The degradation pathways of carbamazepine in advanced oxidation process: A mini review coupled with DFT calculation - Yunyi Li; Ying Yang; Jiamin Lei; Liu, Wen; Meiping Tong; Jialiang Liang (Science of The Total Environment, 2021)
Degradation pathway is important for the study of carbamazepine (CBZ) removal in advanced oxidation processes (AOPs). Generally, degradation pathways are speculated based on intermediate identification and basic chemical rules. However, this semiempirical strategy is sometimes time-consuming and baseless. To improve the situation, a mini meta-analysis was first conducted for the degradation pathways of CBZ in AOPs. Then, the rationality of the pathways was analyzed by Density Functional Theory (DFT) calculation. Results show that the degradation pathways of CBZ in various AOPs has high similarity, and the reactive sites predicted by Fukui function fitted well with the data retrieved from literatures. In addition, molecule configuration of degradation intermediates was found to play a very important roles on degradation pathway. The study reveals that computational chemistry is a useful tool for degradation pathway speculation in AOPs.
Keywords: Fenton; Ozonation; Photocatalysis; PS and PMS; UV